Post-school education in an unequal society - Whitelaw, Emma (School of Economics, 2024)
In South Africa, a country afflicted by conditions of poverty, inequality, and unemployment, a post-school education can be key to fostering upward mobility. However, many of the country's socioeconomic inequalities are replicated within the post-school education system itself. This means that, inter alia, inequalities in student access and success plague the sector despite strides made by the government to redress the educational and economic discrimination of the apartheid regime. In the substantive chapters of this dissertation, I explore inequalities in access, academic achievement, and graduate realities; considering each as an obstacle to equitable participation and success in post-school education, and thereafter. The first substantive chapter concerns access for the 'missing middle'; a group who do not qualify for financial aid but for whom university education is unaffordable. I operationalise the concepts of mobility, vulnerability, and economic stability to differentiate the socioeconomic circumstances of households in South Africa, and locate them within the context of the current post-school funding policy. Results contribute information to an important current policy priority; the development of a sustainable, comprehensive, and progressive financial aid scheme. The second substantive contribution concerns achievement, particularly as it relates to changes in university students' academic performance in 2020 and 2021. Achievement gaps between students funded by the National Student Financial Aid Scheme [NSFAS] and those not funded by NSFAS existed before the COVID-19 pandemic, and the extent to which these were exacerbated by institution closures speaks to issues of participation and success. In my third contribution, I analyse the extent to which financially supporting family and extended family networks is associated with the completion of post-school education. If graduates' realities differ once post-schooling is completed, this can hamper the extent to which post-school education can promote individual upward mobility. A connecting contribution of these chapters is to provide empirical evidence, through rigorous economic analysis, that builds an understanding of inequalities in access, achievement, and graduate realities. This evidence can be inserted into dialogues that shape policies, which ultimately have the potential to disrupt socioeconomic inequalities. Although concerning different stages of post-schooling, all chapters contribute to quantifying features of post-school education that have not previously been explored in-depth